Effect of dietary taurine levels on the conjugated bile acid composition and growth of juvenile Korean rockfish Sebastes schlegeli (Hilgendorf). (17th March 2014) - Kim, Shin‐Kwon; Kim, Kyoung‐Gil; Kim, Kyoung‐Duck; Kim, Kang‐Woong; Son, Maeng‐Hyun; Rust, Michael; Johnson, Ronald
Abstract This study was conducted to investigate the effects of different taurine levels on the conjugated bile acid composition and growth of juvenile rockfish. Five taurine level diets were made by the supplementation of taurine (0%, 0.5%, 1.0%, 1.5% and 2.0%) to a basal diet. Fish meal washed with 70% ethanol to exclude taurine was used for the sole protein source. Feeding experiments were accomplished at 15°C using juvenile fish (initial BW: 13.5 g). Fish were fed the experimental diets for 4 months. At the end of experiments, fish were weighed and stored at −80°C for analysis of free amino acids and conjugated bile acids contents. The growth performance and feed efficiency of Korean rockfish were improved by taurine supplementation in the experimental diets. The taurine contents of the whole body increased with the increase in the taurine supplementation. The primary conjugated bile acids in gall bladder were taurocholic acid (83.5–165.6 mg mL−1) and taurochenodeoxycholic acid (6.3–20.0 mg mL−1). Total bile acids increased with increases in dietary taurine. Taurocholic acid content was more than 95% of the total conjugated bile acids. This indicates that taurine is the sole amino acid to make conjugated bile acid in Korean rockfish. Dietary taurine levels improved the conjugated bile acid composition in juvenile Korean rockfish.